Divalent nanobodies to platelet CLEC-2 can serve as agonists or antagonists - Joanne C. Clark; Eleyna M. Martin; Luis A. Morán; Ying Di; Xueqing Wang; Malou Zuidscherwoude; Helena C. Brown; Deirdre M. Kavanagh; Johan Hummert; Johannes A. Eble; Bernhard Nieswandt; David Stegner; et al. (Communications Biology, 2023)
Fluorescence correlation spectroscopy on crosslinked nanobodies tested on C-type lectin-like receptor 2 (CLEC-2) show different outcomes for divalent and tetravalent nanobody ligands on CLEC-2 clustering, also dependent on CLEC-2 expression levels.